Fomento del diálogo y salud sexual en los estudiantes de décimo de básica en la Unidad Educativa Cicalpa - Chafla Vargas, Karla Abigail (2025)
The research project, "Promoting Dialogue and Sexual Health in Tenth-Grade Students at Cicalpa Educational Unit," arose from a research project within the Basic Education Program, focusing on the development of communication strategies in sexual education for students in upper basic education. The "Comprehensive Sexuality Project" was used as a reference to develop the problem. It was identified that most students lack adequate information on fundamental topics related to sexual well-being, which increases the risk of teenage pregnancies at early ages. The importance of addressing this problem lies in determining the effectiveness of the activities already proposed, which were designed to promote comprehensive teaching that involves both families and the educational community. The main variables that informed the study were dialogue and sexual health; these were essential for strengthening the exchange of ideas among the 13 stakeholders, improving their understanding of caring for their own bodies, and developing habits for making informed and responsible decisions. The objective of this research was to determine the impact and analyze the results obtained from the workshops established under the project. The methodology uses a quantitative approach, with a non-experimental design. The research was based on the type of research: descriptive in scope, basic in objective, cross-sectional in time, and field and bibliographic in location. The results of the research conclusions and recommendations revealed a significant change in the students. It was possible to identify perceptions of the knowledge acquired and changes in attitudes reflected in the survey. This research not only reaffirms the relevance of the courses as an educational tool, but also allows future research to explore the effects of comprehensive sexuality education on adolescents.